PENERAPAN STRATEGI PEMBELAJARAN INQUIRY PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VIII DI MTSN 8 AGAM KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Endang Utama; Iswantir M; Wedra Aprison; Arman Husni (KOLONI, 2022)
The background of this research is the application of inquiry learning strategies in SKI subjects, where the use of inquiry strategies is usually used for general subjects such as science, while the purpose of this research is to find out how the steps for implementing inquiry strategies are in SKI class VIII subjects with material about Daulah Mamluk because SKI subjects are PAI subjects that not only train students to memorize and remember events that have occurred both in the past and the present. However, SKI subjects in the learning process are also needed for students to think critically to analyze or evaluate events that have occurred in the past or in the present. As well as what difficulties occur when implementing inquiry learning strategies in SKI class VIII.3 subjects at MTsN 8 Agam seen from the learning process, with limited learning resources, allocation of learning time, class conditions, facilities and infrastructure that are deemed inadequate and the number of staff the minimum number of educators is only 1 SKI teacher at MTsN 8 Agam. This study uses a descriptive qualitative approach, using the key informants are SKI Mapel Teachers and Students and Supporting Informants are the principals and waka of the curriculum at MTsN 8 Agam, Ampek Angkek District, Agam Regency. In collecting data, the writer uses observation and interview data. The data analysis techniques used are data reduction, data display and data verification. To test the validity of the data by using source triangulation, namely comparing the results of interviews conducted on key informants and supporters with the results of direct observations by the author. The results of this study are 1) The application of inquiry strategy steps in SKI class VIII.3 subjects at MTsN 8 Agam has not been maximized because in its application the SKI teacher has not implemented the syntax of inquiry learning strategies optimally. 2) Teacher difficulties in implementing inquiry learning strategy steps in SKI subjects. SKI teachers have not applied the inquiry step to the step of Testing hypotheses and formulating conclusions according to the syntax of the inquiry strategy correctly due to the lack of time allocation, limited learning resources, student evaluation scores that are still much below the KKM, lack of teaching staff, and inadequate facilities and infrastructure. adequate.  Keyword: Inquiry Learning Strategy, SKI